Harga Diri pada Remaja - Anwar, Fadilla; Alfita, Laili (Universitas Medan Area, 2025)
This research aims to examine adolescent self-esteem factors through a literature review. The main focus is to evaluate what factors influence self-esteem in adolescents. The methodology used is a literature review from various relevant sources. Data was collected using article search techniques via the Researchgate database, Google Scholar, and Google Search using the keyword self-esteem. The data analysis technique used is a Systematic Literature Review. The findings show that adolescents' self-esteem is influenced by several factors: body image, parenting patterns, social support, emotional regulation, and self-acceptance. These teenagers will have high self-esteem when they are satisfied with their body shape, then the support from friends or family and self-acceptance in the environment also make teenagers have high self-esteem. Apart from that, teenagers who have high self-esteem also have high emotional regulation abilities, these teenagers can control the emotions that arise within them, and this cannot be separated from the parenting style given by their parents to these teenagers.